1999
DOI: 10.1177/183693919902400403
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Images of the Child in Early Childhood Education: Reflections and Considerations

Abstract: There have been a number of recent developments impacting on the field of early childhood education that suggest it might be timely to reexamine our understandings of children and childhood. Events such as the development of mandated curriculum for the non-compulsory years, the implementation of diagnostic tools and assessment regimes in the first years of school and moral panic over paedophilia are all underpinned by certain views of the child and ideals of childhood. This article explores how three dominant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 2 publications
0
43
0
1
Order By: Relevance
“…Likely stemming from their ontogenetic roots, the concept of youth is almost universally associated with feelings and emotions, and the concept of adulthood with thinking and cognitive skill (Gino & Desai, 2012;Gray & Wegner, 2009;Loughnan & Haslam, 2007;Woodrow, 1999). An online pilot study confirmed these associations in terms of experience and agency.…”
mentioning
confidence: 99%
“…Likely stemming from their ontogenetic roots, the concept of youth is almost universally associated with feelings and emotions, and the concept of adulthood with thinking and cognitive skill (Gino & Desai, 2012;Gray & Wegner, 2009;Loughnan & Haslam, 2007;Woodrow, 1999). An online pilot study confirmed these associations in terms of experience and agency.…”
mentioning
confidence: 99%
“…The image of the 'innocent child' is a powerful one in contemporary Western culture and in early childhood education (Woodrow, 1999) and, however unintentional, holding this image can result in patronising or coddling practices. In her analysis of the power of public imagery, Holland (1992) discussed how photographs of young children tend to work on the viewer.…”
Section: The Power Of Imagesmentioning
confidence: 99%
“…In case the workers recognize that the performance assessment methods applicable in the organisation are impartial and fair, it promotes the belief on the association and this finally leads to enhanced employees' performance. Woodrow (1999) suggested in the light of Islamic values three fundamental aspects about HRM in an organization, namely performance appraisal, training and empowerment. Along with that, the employees working in the light of IWE and principles could achieve their goals and objectives in better way.…”
Section: Training and The Performance Of Employeesmentioning
confidence: 99%